Effectiveness of Wordwall Education Games (Gaull) to Improve Reading and Writing Skills of 1st Grade Elementary School Students - Nursanti, Ika; Anggraini, Deri (Universitas Nusantara PGRI Kediri, 2025)
This study aims to test the effectiveness of the wordwall education game on improving the reading and writing skills of first-grade elementary school students. This study applies a quasi-experimental method through the